2015
DOI: 10.1208/s12249-015-0425-7
|View full text |Cite
|
Sign up to set email alerts
|

Hot Melt Extrusion: Development of an Amorphous Solid Dispersion for an Insoluble Drug from Mini-scale to Clinical Scale

Abstract: Abstract. The objective of the study was to develop an amorphous solid dispersion (ASD) for an insoluble compound X by hot melt extrusion (HME) process. The focus was to identify material-sparing approaches to develop bioavailable and stable ASD including scale up of HME process using minimal drug. Mixtures of compound X and polymers with and without surfactants or pH modifiers were evaluated by hot stage microscopy (HSM), polarized light microscopy (PLM), and modulated differential scanning calorimetry (mDSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…During dissolution the carrier traps the dispersed API in a high energy state, maintaining supersaturation in the medium over time and preventing crystallization [3]. Bravo et al (2004) reported that HME has many significant benefits such as the elimination of solvents, good content uniformity due to the low drug loading used, dosage forms of a desired shape, including tablets, pellets and implants can be easily manufactured by this process; HME is 2 of 24 also a continuous process and can be scaled up [4] and finally, HME allows conversion of crystalline drugs to amorphous form or dispersion of API into very small particles, enhancing bioavailability and improving patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…During dissolution the carrier traps the dispersed API in a high energy state, maintaining supersaturation in the medium over time and preventing crystallization [3]. Bravo et al (2004) reported that HME has many significant benefits such as the elimination of solvents, good content uniformity due to the low drug loading used, dosage forms of a desired shape, including tablets, pellets and implants can be easily manufactured by this process; HME is 2 of 24 also a continuous process and can be scaled up [4] and finally, HME allows conversion of crystalline drugs to amorphous form or dispersion of API into very small particles, enhancing bioavailability and improving patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…HME has been successfully applied to enhance solubility of poorly soluble drug substance through formation of an amorphous solid dispersion of drug substance in a polymeric (or lipid) carrier matrix (10,11). Proper selection of polymeric carrier, thorough evaluation of physicochemical properties, stability, and performance assessment of an amorphous solid dispersion are key aspects that should be evaluated to ensure successful development of bioavailable dispersion by HME process (12,13). However, to develop a commercial dosage form the solid dispersion needs to be converted to a final dosage form such as tablets or capsules.…”
Section: Introductionmentioning
confidence: 99%
“…SD formulation of antiulcer drug lafutidine was successfully formulated using hot melt extrusion (HME) technique, and it was demonstrated that the SD of lafutidine performed better with immediate drug release as compared with pure lafutidine [19]. Agrawal et al developed SDs using HME technology with a scale up from mini scale to clinical scale [20].…”
Section: Melt Extrusion Methodsmentioning
confidence: 99%